(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Background: Pregnant women with COVID-19 disease are at increased risk of severe illness with greater risk of intensive care unit admission, mechanical ventilation & even death specially in 3rd trimester. Pregnancy greater than 20 weeks with severe maternal illness have five times more ICU admission than pregnancy before 20 weeks. Objective: Clinical evaluation of course of COVID-19 disease among Covid positive pregnant women to raise awareness emphasizing preventive measure, to seek early medical care & to have an institutional protocol for maternity care during pandemic. Methods: A prospective observational study in a single tertiary pandemic centre in CMOSHMC during 15th March to 15th October 2021. All pregnant women admitted with sign symptom of COVID-19 disease, RT-PCR +ve, HRCT+ve or both included in the study. Total 2639 patient admitted with in COVID-19 disease in the study period 54% were female & among them 64 (2.4%) were pregnant.Out of 64 pregnant mother 20(31%) were admitted in ICU,61(95%) in 3rd trimester 29 to39 weeks, 2 previable (aborted) & 1 in postpartum period.Among 61patient, 23 delivered 11 (48%) vaginal,12(52%) cesarean section &7 (11%) died. Indication of cesarean section 3 were for severe&critical covid status & rest 9 were for obstetric cause. 38(60%) patient recovered from covid disease among them 10(16%) from those admitted in ICU & discharged on D16 to D21 with advise for Antenatal checkup & institutional delivery later on. Planned cesarean section for 3rd gravida 39 weeks pregnancy P/ H/O 2 cesarean section was delayed for 10 days after resolution of symptom &cesarean section done at 40+3 weeks, both the mother & baby were healthy. Among patient admitted in ICU lung involvement were 50 to 90 % in HRCT & treatment was given according to guideline inj. Enoxypyrine,Inj. Ramdisivir, steroid &Tocillizumeb.SPO2 maintained by O2 progressively through nasal canula, face mask, HFNC (20patient)& mechanical ventilation in 4patient. Among 7 death 2 died in antenatal period one from cardiac arrest &1 from cardiorespiratory failure (admitted with SPO2 37%). Rest 5 died in postnatal period 3 after cesarean, 2 being for severe Covid status, one for obstetric indication onD9 in hyper immune state & 2 after vaginal delivery. All 7 patient had lung involvement 70 to 90% in HRCT,Out of 23 delivery, 8 were preterm birth with 1 IUD &15 delivered at term. Five neonate were admitted in NICU for prematurity, IUGR for observation. Breast feeding & skin to skin contact were encouraged. All neonate were RTPCR- ve, 2 neonate died on D13 &D17 due to prematurity & IUGR. Conclusion: Critical review was done to prepare an institutional protocol to optimize care & to reduce risk of severe illness & death .All patient & support partner should be counselled about infection preventive measure, risk factor reduction & importance of seeking medical care early once symptom develop. Bangladesh J Obstet Gynaecol, 2021; Vol. 36(1): 33-41